FARMERS-HERDERS CONFLICTS AND FOOD INSECURITY IN NIGERIA - DAUPAMOWEI HENRY ASANEBI (International Studies Journal)
The past few years have seen an upsurge in farmers and herders conflicts in Nigeria, especially in the North Central, North East, and South East regions of the nation, making Nigeria high in the index of unsafe nations around the globe. These conflicts have a terrible impact on the economy of the country, which is already suffering from food shortages and insecurity as well as constant price rises for food. As a result of the aforementioned, the paper focuses on investigating the root causes of farmers-herdsmen conflicts and how these conflicts affect the availability and cost of basic staple foods. A qualitative research approach was adopted, and data were gathered through a thorough desk literature review. The Thomas Malthus Resource Scarcity theory was adopted, which underpinned the conflagration between farmers and herders over competition for available limited resources such as grazing lands and water, etc. The paper makes the case that persistent farmers-herders conflicts have an impact on (i) food shortages and insecurity, as many farmers were compelled to flee their farms for safety. The contention is that in a crisis situation, agricultural activities would either cease to exist or cannot flourish; (ii) result in price increases for scarce foods; and (iii) inevitably lower people's standard of living. Furthermore, given the rise in tensions between farmers and herdsmen and the significant implications for the nation, the study recommends the Nigerian government enact stringent agricultural policies that support agricultural activities in order to ensure food security while also providing grazing lands for herders in their area.